A database of cancer induction by low-dose radiation in mammals: overview and initial observations. (1st January 2003) - Duport, P.
The lifespan studies of animals exposed to low doses of ionizing radiation with a view to determining the relationships between radiation dose and cancer incidence have been identified and corresponding publications have been reviewed. The information on experimental conditions and cancer incidence data in exposed and control animals have been entered into a database intended for a global analysis of the relationship between low doses of ionizing radiation and cancer incidence. Data concerning about 85, 000 exposed animals and their 45, 000 corresponding controls, with a total of over 60, 000 and 12, 000 cancers in exposed and control animals, respectively, have been collected. Experiments were conducted with all types of ionizing radiation, at doses ranging from 10 mGy to 3.3 Gy for gamma radiation, 40 mGy to 4 Gy for X-rays, 2 mGy to several hundred Gy for beta radiation, 2 mGy to 9 Gy to alpha radiation, and 5 mGy to 3.3 Gy of neutrons. Within a specific experiment, data are grouped into datasets, which concern animals of a particular species, strain, sex, age at exposure, exposed to a range of doses under specific exposure conditions. In this body of data, no cancers were observed in the control groups of about 30% of the datasets, which makes it impossible to detect a possible decrease in cancer rates in exposed animals. When cancers were observed in control animals, either no effect or an apparent reduction in cancer risk was observed in 40% of the datasets for neutron exposure, 50% of the datasets for X-rays, 53% of the datasets for gamma radiation, and 61% of the datasets for alpha radiation. Apparent reductions in cancer rate, significant at up to 10 standard deviations, were observed in mice exposed to 100 and 250 mGy of gamma radiation. This review confirmed that, in some experiments, exposed animals live considerably longer (up to 40%) than their controls. In some experiments for which pathological observations were reported on non-malignant diseases, there appears to be apparent beneficial effects of low doses of radiation, coupled with an apparently increased longevity. The statistical strength of the overall observations has not been determined yet and is subject to further work. However, the frequency of an apparent lack of effect or of protective effects, and of increased longevity in exposed animals, challenges the general validity of the Linear No Threshold Theory (LNT) and calls for research aimed at confirming or disproving the existence of beneficial effects of low-dose radiation on malignant and nonmalignant diseases and at determining the mechanisms that subtend them.